Comparison of phenol content and antioxidant capacity of nuts - Abe,Lucile Tiemi (2010)
Frequent nut intake is associated with protective effects against cardiovascular diseases. In addition to the generally high contents of unsaturated fatty acids, polyphenol compounds seem to be also implicated in health promoting effects of nuts due to their antioxidant properties. In this way, eleven different kinds of nuts, including pinhao seeds (Araucaria angustifolia) and Brazil nuts (Bertholletia excelsa), typical of Brazil, were analyzed for the content of phenol compounds, including the potent anti-mutagenic and anti-cancer ellagic acid, and antioxidant capacity of methanolic extracts. The antioxidant capacity varied a hundred times among the different nuts, from 1.2 to 120 mg of Trolox equivalents.100 g-1 (FW). Total ellagic acid was determined after acid hydrolysis of ellagitannins and ellagic acid glycosides, and it was detected in only 3 of the 11 samples. The content of free and total ellagic acid in nuts varied from 0.37 to 41 and from 149 (chestnuts) to 823 (walnuts) mg.100 g-1 (FW), respectively. Among nuts, samples with the highest contents of ellagic acid (walnuts and pecans) also presented the highest total phenol contents and DPPH radical scavenging capacities. Pinhao seeds and Brazil nuts did not present significant amounts of phenols nor antioxidant capacity.